The Influence of Service Quality and Price on Customer Satisfaction at AHHAS Karya Perdana Workshop - Surianti, Surianti; Falsah , Andika Rafid (Gema Wiralodra, 2023)
The AHHAS Karya Perdana workshop is located on Jl. DI. Panjaitan, Karanganyar, Kec. Indramayu, Indramayu Regency, West Java 45213. The workshop provides a complete range of spare parts products and motor vehicle repair services. The workshop has a very comfortable waiting room atmosphere, quality of service is a priority with varying prices, and a strategic workshop location in the city center makes it easy for the people of Indramayu to find and repair motorbikes, influencing customer satisfaction. The method used in this study uses descriptive and associative research methods using a quantitative approach. This study's sample number was 95 AHHAS Karya Perdana Workshop customers. By collecting data using a questionnaire. Data analysis technique using multiple linear regression analysis, correlation, and coefficient of determination. Calculations using the SPSS software tool version 20. The results showed that service quality and price significantly and positively affected customer satisfaction. In this study, service quality and price can explain customer satisfaction by 62.1%, while the remaining 37.9% is influenced by factors not examined.